2018
DOI: 10.1113/jp276735
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training reduces the insulin‐sensitizing effect of a single bout of exercise in human skeletal muscle

Abstract: Key points A single bout of exercise is capable of increasing insulin sensitivity in human skeletal muscle. Whether this ability is affected by training status is not clear. Studies in mice suggest that the AMPK‐TBC1D4 signalling axis is important for the increased insulin‐stimulated glucose uptake after a single bout of exercise. The present study is the first longitudinal intervention study to show that, although exercise training increases insulin‐stimulated glucose uptake in skeletal muscle at rest, it di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 65 publications
(143 reference statements)
6
57
4
Order By: Relevance
“…Numerous studies have shown that aerobic exercise training increases hexokinase protein and activity levels ~25–100% in both human and rodent skeletal muscle [163,164,165,166,167,168,169,170,171,172]. In contrast, the effects of resistance exercise training on muscle hexokinase levels is less clear.…”
Section: Skeletal Muscle Glucose Metabolismmentioning
confidence: 99%
“…Numerous studies have shown that aerobic exercise training increases hexokinase protein and activity levels ~25–100% in both human and rodent skeletal muscle [163,164,165,166,167,168,169,170,171,172]. In contrast, the effects of resistance exercise training on muscle hexokinase levels is less clear.…”
Section: Skeletal Muscle Glucose Metabolismmentioning
confidence: 99%
“…A single bout of exercise can have long-lasting metabolic effects (Richter, Mikines, Galbo, & Kiens, 1926;Steenberg et al, 2019;Sylow et al, 2019). Therefore, to determine if a single night of wheel running could affect liver responsiveness to epinephrine, the previous experiment was repeated, however, exercised mice (EX) ran on wheels for only one night (16:00-08:00 hr) instead of 12 days.…”
Section: Acute Vwr Does Not Induce Liver Epinephrine Resistancementioning
confidence: 99%
“…In a recent study, Steenberg et al [36] found that exercise training history diminishes the ability of a single bout of exercise to enhance insulin sensitivity, albeit not specifically pertaining to the postprandial response. Nonetheless, while our participants were not “trained” and had ceased any significant physical activity for 1 week before the initial trial, they did have experience playing football.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, while our participants were not “trained” and had ceased any significant physical activity for 1 week before the initial trial, they did have experience playing football. Steenberg et al [36] reported that exercise training increases insulin-stimulated glucose uptake of skeletal muscle at rest, but with no further gains in the acutely exercised leg. Thus, the elevated levels of glycogen in muscle after training might reduce the ability of acute exercise to enhance insulin-stimulated glucose uptake through an attenuation of activated protein kinase activity and may be applicable in our findings.…”
Section: Discussionmentioning
confidence: 99%